Elemental and Sr-Nd isotopic geochemistry of Cretaceous to Early Paleogene granites and volcanic rocks in the Sikhote-Alin Orogenic Belt (Russian Far East): implications for the regional tectonic evolution. (15th September 2017) - Zhao, Pan; Jahn, Bor-ming; Xu, Bei
Graphical abstract: Highlights: Cretaceous-Paleogene granites and volcanic rocks were identified in the Sikhote-Alin Belt. Mixing of mantle-derived juvenile and recycled crustal components was suggested for the generation of felsic magmatic rocks. A Late Mesozoic-Early Cenozoic magmatic belt was proposed along the southeastern margin of NE Asia. Abstract: The Sikhote-Alin Orogenic Belt in Russian Far East is an important Late Mesozoic to Early Cenozoic accretionary orogen related to the subduction of the Paleo-Pacific Plate. This belt was generated by successive accretion of terranes made of accretionary prisms, turbidite basins and island arcs to the continental margin of northeastern Asia (represented by the Bureya-Jiamusi-Khanka Block) from Jurassic to Late Cretaceous. In order to study the tectonic and crustal evolution of this orogenic belt, we carried out zircon U-Pb dating, and whole-rock elemental and Sr-Nd isotopic analyses on granites and volcanic rocks from the Primorye region of southern Sikhote-Alin. Zircon dating revealed three episodes of granitoid emplacement: Permian, Early Cretaceous and Late Cretaceous to Early Paleogene. Felsic volcanic rocks (mainly rhyolite, dacite and ignimbrite) that overlay all tectonostratigraphic terranes were erupted during 80–57 Ma, postdating the accretionary process in the Sikhote-Alin belt. The Cretaceous-Paleogene magmatism represents the most intense tectonothermal event in the Sikhote-Alin belt. Whole-rock major and trace elemental data show arc-like affinity for granitoids and volcanic rocks, indicating that they were likely generated in a supra-subduction setting. Their initial 87 Sr/ 86 Sr ratios range from 0.7048 to 0.7114, and εNd (t) values vary from +1.7 to −3.8 (mostly < 0). Thus, the elemental and Sr-Nd isotopic data suggest that the felsic magmas were generated by partial melting of source rocks comprising mantle-derived juvenile component and recycled crustal component. In addition to the occurrence in the Sikhote-Alin orogenic belt, Cretaceous to Early Paleogene magmatic rocks are also widespread in NE China, southern Korean peninsula, Japanese islands and other areas of Russian Far East, particularly along the coastal regions of the Okhotsk and Bering Seas. These rocks constitute an extended magmatic belt along the continental margin of NE Asia. The generation of this belt was ascribed to subduction of the Paleo-Pacific Plate.